Implementation of a telemental health service for medical students during the COVID-19 pandemic - Liberal,Suzana Pacheco (2021)
Abstract: Introduction: The COVID-19 pandemic can be considered a severely stressful event and trigger negative repercussions on the mental health of medical students, such as psychological distress and the development or worsening of mental disorders, harming the academic, social and professional life of these students. As a result of the interruption of classes and the social distancing measures advocated by health agencies during the pandemic, the mental health care sector for medical students at the Federal University of Rio de Janeiro (UFRJ) needed to cancel the face-to-face care at the Clementino Fraga Filho University Hospital in early March 2020 and think of other forms of mental health care for these students. Experience report: This is an experience report about the implementation of telemental health care for medical students at UFRJ during the pandemic, for the continuity of mental health care program using remote assistance, started in late March 2020. The service is being offered by a team of five psychiatrists, a psychologist and a social worker, all university employees. Discussion: The teleservice has served as an important space for listening and embracement in face of these students’ psychosocial demands, whose challenge consists in overcoming some barriers that hinder the availability of and access to mental health services on the university campus, including the preservation of the doctor-patient relationship, the guarantee of confidentiality and quality, and the offer of a space for mental health care when the physical presence is not possible. Conclusion: Despite the difficulties inherent in the rapid process of implementing this service, the potential of technology to help the population at this critical moment is perceived, especially regarding the attention to the mental health of specific groups, such as medical students. The telehealth represents a potential for learning and change in the ways how the access to care is offered, with the perspective of bringing benefits to the students’ mental health, even after the current period of the pandemic, with the goal of expanding these services to other courses of the UFRJ.